2010
DOI: 10.1037/a0017430
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of creative styles and personality types between American and Taiwanese college students and the relationship between creative potential and personality types.

Abstract: The purpose of the study was to compare differences in creative styles (Kirton, 1976) and personality types between Americans and Taiwanese and to examine the relationships among various personality types and creative potential. Creative potential was measured by the Torrance Test of Creative Thinking-Figural, and personality types were measured by the Keirsey Temperament Sorter II. Ninety-three American and 76 Taiwanese college students specializing in teacher education participated in this study. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
(109 reference statements)
1
12
0
5
Order By: Relevance
“…However, it is inconsistent with Torrance's (1990) and Cramond et al's (2005) claims that the two versions measure two different sides of one general creativity factor, because Torrance (1990) might have used a smaller number of participants than Clapham (2004) and Ulger (2015) elaboration skills (to focus, think in-depth and express complex thoughts) whereas males are best at original imagination, which respectively best predict their creative thinking skills. This is consistent with previous studies' findings, that due to their attention to detail and their persistence, females are best at inbox thinking and elaboration skills, whereas males are best at outbox imagination (e.g., Cheng, Kim, & Hull, 2010;Kim, Cramond, & Bandalos, 2006;Kim, Lee, Chae, Andersen, & Lawrence, 2011;Razumnikova, Volf, & Tarasova, 2009). This might be because traditionally females are expected to conform to rules more than males (Bender, Nibbelink, Towner-Thyrum, & Vredenburg, 2013;Charyton, Elliott, Rahman, Woodard, & DeDios, 2011;Cogérino, Bois, & Amorose, 2006;Razumnikova, 2002;Stoltzfus, Nibbelink, Vredenburg, & Thyrum, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…However, it is inconsistent with Torrance's (1990) and Cramond et al's (2005) claims that the two versions measure two different sides of one general creativity factor, because Torrance (1990) might have used a smaller number of participants than Clapham (2004) and Ulger (2015) elaboration skills (to focus, think in-depth and express complex thoughts) whereas males are best at original imagination, which respectively best predict their creative thinking skills. This is consistent with previous studies' findings, that due to their attention to detail and their persistence, females are best at inbox thinking and elaboration skills, whereas males are best at outbox imagination (e.g., Cheng, Kim, & Hull, 2010;Kim, Cramond, & Bandalos, 2006;Kim, Lee, Chae, Andersen, & Lawrence, 2011;Razumnikova, Volf, & Tarasova, 2009). This might be because traditionally females are expected to conform to rules more than males (Bender, Nibbelink, Towner-Thyrum, & Vredenburg, 2013;Charyton, Elliott, Rahman, Woodard, & DeDios, 2011;Cogérino, Bois, & Amorose, 2006;Razumnikova, 2002;Stoltzfus, Nibbelink, Vredenburg, & Thyrum, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Another similar measure is the Keirsey Temperament Sorter (KTS II; Keirsey, 1998), which is viewed as an alternative to the MBTI (Cheng, Kim, & Hull, 2010) with the advantages of quicker and easier scoring, shorter administration time (about 15 minutes), and lower cost. Several studies have confirmed the usefulness of the KTS II as a personality indicator (Russo, Mertins, & Ray, 2013;Varlami & Bayne, 2007).…”
Section: Jung's Theory Of Personality Typesmentioning
confidence: 99%
“…This belief is shared by other researchers. [19][20][21] David sees engineers as two types of people, those who break the world into manageable chunks and those who synthesize and connect the dots to innovate and create opportunities: …”
Section: "So Again (Innovativeness) Is Creativity In Some Respects …Imentioning
confidence: 99%